1995
DOI: 10.1366/0003702953965290
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Surface Adsorption Behavior of High- and Low-Density Lipoproteins as Analyzed by FT-IR/ATR Spectroscopy

Abstract: The adsorption behavior of high-density lipoprotein (HDL) and low-density lipoprotein (LDL) onto a zinc selenide crystal surface and cholesterol-modified ZnSe crystal surface has been studied in terms of adsorption kinetics and isotherms with the use of the FT-IR/ATR technique. Adsorption kinetic plots indicated that the adsorption equilibrium of HDL and LDL is reached at 30–40 min, which is similar to the case for other proteins. From the adsorption isotherms of HDL and LDL, transitions from monolayer adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…Quantitatively, these authors found a lower adsorbed amount for silica than we do in the present investigation, which might be due to the use of lipoproteins from different sources or differences in the buffer system employed. Furthermore, Hu and Singh (29) found the adsorption of HDL to be significantly higher at zinc selenide than at cholesterol-modified zinc selenide surfaces, again qualitatively in line both with the findings of the present investigation on HDL adsorption at silica and methylated silica and with the higher adsorption at silica also for the other lipoproteins.…”
Section: Adsorption At Silica and Methylated Silicasupporting
confidence: 91%
“…Quantitatively, these authors found a lower adsorbed amount for silica than we do in the present investigation, which might be due to the use of lipoproteins from different sources or differences in the buffer system employed. Furthermore, Hu and Singh (29) found the adsorption of HDL to be significantly higher at zinc selenide than at cholesterol-modified zinc selenide surfaces, again qualitatively in line both with the findings of the present investigation on HDL adsorption at silica and methylated silica and with the higher adsorption at silica also for the other lipoproteins.…”
Section: Adsorption At Silica and Methylated Silicasupporting
confidence: 91%
“…Film Formation. The first exposure of HDL and LDL to gold results in adsorption profiles similar to those observed by Hu et al on ZnSe substrates 34 and Hlady et al on hydrophilic silica. 32 On these hydrophilic surfaces, the adsorption of HDL and LDL was found to be transportlimited, with the majority of the response occurring in the first 5 min.…”
Section: Properties Of Lipoprotein Filmssupporting
confidence: 78%
“…33 Hu et al studied the adsorption of HDL and LDL onto ZnSe crystal surfaces, and those surfaces modified with cholesterol, by Fourier transform infrared spectroscopy (FTIR) in combination with attenuated total reflectance spectroscopy (ATR). 34 In this paper, we will show how the TSM can be used to characterize LP films formed over gold surfaces. We will demonstrate how an oscillator circuit featuring AGC can be used to determine the mass of a viscoelastic LP film in the presence of liquid.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we investigated the HDL and LDL adsorption behavior in terms of kinetics and isotherms to analyze their cholesterol binding properties using FT-IR with ATR accessory. Adsorption isotherms revealed monolayer to multilayer adsorption transitions of HDL and LDL (19). These results also indicated significant differences in the adsorption behavior of HDL and LDL, which was affected considerably by cholesterol (Fig.…”
Section: Application Of Protein Adsorption Analysis By Ir Spectroscopymentioning
confidence: 63%
“…In transmission mode, high concentration of proteins (> lmg/ml) are required to obtain accurate protein spectra. For protein adsorption studies, or for studies with solid powder and thin films, ATR accessory is most commonly used (5,18,19) for sampling. One of the advantages of ATR technique in recording protein spectrum is the avoidance of solvent interference in IR spectra, because it limits the effective sample thickness to a thin layer near the surface of an internal reflection element (crystal) (20).…”
Section: Ir Spectroscopy Of Proteins and Peptidesmentioning
confidence: 99%